Cloning and characterization of phosphoglucose isomerase in Lentinula edodes. (23rd February 2022) - Wang, Yunxiao; Chen, Juhong; Han, Jing; Yang, Zhengyan; Zhu, Jing; Ren, Ang; Shi, Liang; Yu, Hanshou; Zhao, Mingwen
Abstract: Phosphoglucose isomerase (PGI) is a key enzyme that participates in polysaccharide synthesis, which is responsible for the interconversion of glucose‐6‐phosphate (G‐6‐P) and fructose‐6‐phosphate (F‐6‐P), but there is little research focusing on its role in fungi, especially in higher basidiomycetes. The pgi gene was cloned from Lentinula edodes and named lepgi . Then, the lepgi ‐silenced strains were constructed by RNA interference. In this study, we found that lepgi ‐silenced strains had significantly less biomass than the wild‐type (WT) strain. Furthermore, the extracellular polysaccharide (EPS) and intracellular polysaccharide (IPS) levels increased 1.5‐ to 3‐fold and 1.5‐fold, respectively, in lepgi ‐silenced strains. Moreover, the cell wall integrity in the silenced strains was also altered, which might be due to changes in the compounds and structure of the cell wall. The results showed that compared to WT, silencing lepgi led to a significant decrease of approximately 40% in the β‐1, 3‐glucan content, and there was a significant increase of 2‐3‐fold in the chitin content. These findings provide support for studying the biological functions of lepgi in L. edodes .